2012
DOI: 10.1089/lap.2011.0235
|View full text |Cite
|
Sign up to set email alerts
|

Transumbilical, Single-Port, Totally Extraperitoneal, Laparoscopic Inguinal Hernia Repair Using a Homemade Port and a Conventional Instrument: An Initial Experience

Abstract: A transumbilical, single-port, TEP laparoscopic hernioplasty using a homemade port and a conventional instrument permitted nearly scarless surgery for the treatment of inguinal hernias. Further studies are necessary before this approach can be recommended as a standard procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…On further scrutiny, 16 articles 15,19,22,[35][36][37][38][39][40][41][42][43][44][45][46][47] were used in our literature review and 3 studies comparing LESS TEP with LAP TEP were found to have useful data for the summative outcome. One study commented on a previous report.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On further scrutiny, 16 articles 15,19,22,[35][36][37][38][39][40][41][42][43][44][45][46][47] were used in our literature review and 3 studies comparing LESS TEP with LAP TEP were found to have useful data for the summative outcome. One study commented on a previous report.…”
Section: Resultsmentioning
confidence: 99%
“…15,19,35,37,38,41,42,44,47 Seven studies used a single port access device. 15,19,36,38,39,41,43 Other techniques included the use of 3 ports through a single incision.…”
Section: Surgical Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…However, almost all SIL-TEP study reported before were operated through the space of the front of the posterior sheath of rectus abdominis and then enter the PPS for further operation. [ 5 , 9 , 14 , 15 ] Though many physicians have focused on the preperitoneal (posterior) space many years, [ 12 , 13 ] there was few evidence verified SIL-TEP through PPS was feasible and safe for inguinal hernia repairing. For our SIL-TEP procedure is conducted all in PPS, the procedure was named as SIL-TPP, for distinguishing with SIL-TEP.…”
Section: Introductionmentioning
confidence: 99%